2016
DOI: 10.1590/1980-5497201600010014
|View full text |Cite
|
Sign up to set email alerts
|

Genotypes distribution of human papillomavirus in cervical samples of Ecuadorian women

Abstract: Viral genotypes different from HPV 16 and HPV 18 are frequently detected among Ecuadorian women. The overall prevalence of HPV resulted higher than the one reported in other South American countries with a greater burden in the second and third decades of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 16 publications
2
8
0
3
Order By: Relevance
“…We found HPV16 in 19 (41.30%), HPV18 in 9 (19.57%), and HPV45 in 1 (2.17%) of HPV positive samples. Human papillomavirus16 and HPV18 had the highest frequencies in cervical cancer (22,41), which is similar to our result. Another result showed that the frequencies of HPV35 and HPV31 were the highest (32), which is inconsistent with our result.…”
Section: Discussionsupporting
confidence: 92%
“…We found HPV16 in 19 (41.30%), HPV18 in 9 (19.57%), and HPV45 in 1 (2.17%) of HPV positive samples. Human papillomavirus16 and HPV18 had the highest frequencies in cervical cancer (22,41), which is similar to our result. Another result showed that the frequencies of HPV35 and HPV31 were the highest (32), which is inconsistent with our result.…”
Section: Discussionsupporting
confidence: 92%
“…However, Salehi-Vaziri et al reported that the most common HPV genotypes in Iranian women were HPV 16 and 53 [16]. García Muentes et al reported that the most common HPV genotypes in Ecuadorian women were HPV 16 and HPV 33 [17].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors suggest that the presence of these genotypes (high-grade lesions) would be more likely to progress to cervical cancer than other HPV types; this is due to the oncogenic potential of these genotypes [41]. …”
Section: Discussionmentioning
confidence: 99%